Multiparametric comparison of thermal welding versus cold knife tonsillectomy with tonsil size - Çelebi, Şaban; Çelik, Öner; Tepe Karaca, Çiğdem; Ulusoy, Seçkin (ENT Updates, 2013)
Objective: This study is performed to compare thermal welding tonsillectomy (TWT) technique versus cold knife tonsillectomy (CKT) technique under consideration of postoperative pain, intraoperative bleeding, operation time, and tonsil size. Methods: One hundred and three patients underwent tonsillectomy aged between 5 and 39 years were included into the study. Tonsil sizes were classified with Brodsky’s tonsil scale system ranging from 0-4. Duration of the operation and the amount of bleeding were recorded. Postoperative pain was evaluated via visual analogue scale and face pain scale on the 1st, 3rd, 7th and 14th postoperative days. Results: Mean operative time was lower in TWT group than CKT group (p0.05). Conclusion: In the present study, it was concluded that the tonsil size does not affect the amount of intraoperative bleeding however increase in the tonsil size decreases the postoperative pain.